2023
DOI: 10.3390/su15021020
|View full text |Cite
|
Sign up to set email alerts
|

The Multidimensional Measurement Method of Urban Sprawl and Its Empirical Analysis in Shanghai Metropolitan Area

Abstract: Urban sprawl concerns the high-quality and sustainable development of large cities. Due to the ambiguous definition, diversity of measurement indices and complexity of the driving mechanism of urban sprawl, the research results are rich but controversial. How does one carry out multidimensional measurement of urban sprawl? How does one reveal the spatio-temporal evolution characteristics of urban sprawl dynamically? First, according to the three common characteristics of urban sprawl (discontinuity of land use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The DMSP-OLS dataset covers 1992 to 2013 and offers nighttime light data at a spatial resolution of 1 km by 1 km. In contrast, the NPP-VIRS dataset spans from 2012 to 2020, offering higher spatial resolution data at 500 m by 500 m [22]. These datasets capture the artificial illumination at night, allowing for the assessment of urbanization trends, economic activity, and population distribution across regions.…”
Section: Nighttime Lights (Ntl) Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The DMSP-OLS dataset covers 1992 to 2013 and offers nighttime light data at a spatial resolution of 1 km by 1 km. In contrast, the NPP-VIRS dataset spans from 2012 to 2020, offering higher spatial resolution data at 500 m by 500 m [22]. These datasets capture the artificial illumination at night, allowing for the assessment of urbanization trends, economic activity, and population distribution across regions.…”
Section: Nighttime Lights (Ntl) Datamentioning
confidence: 99%
“…This includes mapping how cities grow and creating models that show economic and environmental factors like Gross Domestic Product (GDP) and electricity use. Studies have been conducted to uncover the impacts of human activities and light pollution on both ecosystems and human health [19,22]. Furthermore, using freely available datasets, which offer a detailed view at a 30 m resolution, researchers have discovered that they provide more accurate information about land use patterns [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al developed a fringe extraction model of small-and medium-sized urban areas by using a set of data sources including high-resolution imagery from the GF-2 satellite, the WorldPop dataset, and POI [17]. Shi et al stress that the metropolitan fringe area should be identified from a multi-dimensional perspective and propose an identification index system including indicators such as discontinuous land use, increasing population density, and fluctuating land use efficiency [18]. In addition to the increasing diversity of datasets that have been used to delineate the metropolitan fringe area, some studies have developed more complex mathematical methods by using machine learningrelated algorithms.…”
Section: The Functional and Morphological Approaches To Delineating M...mentioning
confidence: 99%
“…More recently, metropolitan fringe areas have been delineated in a more quantitative and non-subjective way. Within this line of the literature, existing studies have drawn upon a variety of datasets such as remote sensing images [11,12], nighttime lights [13][14][15], points of interest (POI) [16], or a combination of some of these data sources [17][18][19][20]. Importantly, no matter which types of data have been used to delineate the metropolitan fringe area, the rationales behind these quantitative delineation methods are generally similar.…”
Section: Introductionmentioning
confidence: 99%
“…Global experience has shown that growing megacities also often experience significant changes in their functional and spatial patterns [73], especially in China's megacities [74]. It has been demonstrated that urban expansion increases the demand for transport to the urban fringe, while improved transport conditions will in turn affect the city by enhancing the accessibility of the urban fringe, which in turn triggers the evolution of the land-use structure and promotes faster outward development of the city [75].…”
Section: Urban Expansion Along Suburban Railwaysmentioning
confidence: 99%